The Fundamental Right to Secrecy of Communications - Díaz Revorio, Francisco Javier (2006)
This paper analyses the fundamental right to privacy of communications. This right is protected by Spanish law, but it is also internationally recognised, being enshrined in Article 12 of the Universal Declaration of Human Rights, and in other international treaties. The author points out that although the interception of communications may be necessary in certain cases, and as defined by law, this measure should be considered as an exception to the rule, precisely because this right is intended to protect the privacy of individuals. It is therefore imperative that such intrusion into this private sphere be clearly defined and regulated by law, in order to prevent possible violations in this subject.